PENGUATAN KAPASITAS KELOMPOK USAHA MIKRO MELALUI DIGITAL MARKETING DI DESA UNGASAN KECAMATAN KUTA SELATAN - Anak Agung Istri Setiari JMH; Putu Ratna Windusara Putri,; I Made Sujana; Yoviniani Yevri Yanseni (Yayasan Nusantara Hasana Berdikari, 2023)
This community service program aims to increase the capacity of micro-enterprise groups in Ungasan Village, South Kuta District, through the use of digital marketing as a business development strategy. The main problems faced by micro-enterprises include limited knowledge of digital marketing, poor social media management skills, and the suboptimal use of digital platforms to expand markets. Digital marketing can expand market reach and increase the competitiveness of MSMEs. The community service program was implemented through counseling, training, and mentoring on the practical use of business social media, marketplaces, and the creation of digital promotional content. The results of the activity showed an increase in participants' understanding of digital marketing strategies and an increase in their ability to utilize digital technology to support micro-enterprises.